Penerapan Metode Algoritma Fisher Yates Shufle Pada Game Edukasi Ragam Budaya Berbasis Android - Trisna Aditiya; Noni Juliasari; Pipin Farida Ariyani (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2022)
In this day and age, gaming has become a hobby for everyone. Starting from children, teenagers and adults. The use of educational games as learning media for the introduction of regional culture is considered suitable, because it can take advantage of developing technology. The way for children to get to know about the diversity of Indonesian culture is to play games with Indonesian cultural backgrounds. Therefore it is necessary to make educational game applications. Educational games about local wisdom were chosen so that children can still play while learning or getting to know food, house, and regional dances in Indonesia while still being able to play. This is considered effective in increasing children's knowledge about Indonesian culture without being forced to study. The game that will be made is not only an educational genre but also a quiz genre where the order of questions and the order of answers that appear will be randomized using the Fisher Yates Algorithm method. This Indonesian Cultural Variety educational game was developed using the Multimedia Development Life Cycle (MDLC) method which consists of six stages, namely concept, design, collecting material, assembly, testing and distribution. This Indonesian Cultural Variety educational game can be played on Android with a minimum of Android 6.0 software or commonly called marshmallow. Based on the results of tests involving 10 respondents, a good response was obtained because it got a percentage of 94.6%.